IDENTIFIKASI MINAT BELAJAR MATEMATIKA SISWA SMP MUHAMMADIYAH 1 TARAKAN DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Rahayu, Setia Widia (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2021)
The learning process underwent a surprising change, due to the Covid-19 pandemic. The Minister of Education makes a decision to implement online learning. Because learning is carried out online, teachers and students must continue to adjust learning which is usually face-to-face, this is only through virtual. Researchers conducted observations at SMP Muhammadiyah 1 Tarakan, obtained information that in the implementation of online learning, students were often late for zooming, and sometimes students did not attend learning activities via zoom. Assignments given by the teacher are often late for students to collect. In addition to observations, interviews with mathematics teachers were also conducted, he provided information that the low enthusiasm of students to learn online, students' readiness to learn seemed to be lower than in direct learning. From the problems that appear in the field, the author is interested in conducting a research entitled